EVALUATION OF HUMAN UMBILICAL CORD BLOOD AS A SOURCE OF EMBRYONIC STEM CELLS - Hussain, Issam; Magd, Salah A; Eremin, Oleg; El-Sheemy, Mohamed (European Scientific Journal, ESJ, 2013)
Human umbilical cord blood (HUCB) has been poorly characterised as a source of embryonic stem cells (ESCs). The aim of this study, therefore, was to evaluate HUCB as source of mesenchymal stem cells (MSCs) with embryonic characteristics. HUCB was collected from consenting women undergoing elective caesarean sections. HUCB was meticulously explanted into MesenCult media and incubated. Qualitative and quantitative immunophenotyping of cells was achieved using fluorescein isothiocyanate (FITC) labelled antibodies (CD34, CD45, CD29, CD44, CD73 and CD105) phenotypic markers. Immunocytochemistry was carried out for the human ESC markers CD9, stage-specific embryonic antigen-1 and 4 (SSEA-1 and SSEA-4), E-cadherin, Podocalyxin (PODXL), sex-determining region Y-box 2 (SOX2), NANOG and Octamer (OCT3/4). MSCs were cultured to induce differentiation into adipogenic, osteogenic, chondrogenic and neurogenic cells. Immunocytochemistry was used to identify fatty acid binding protein-4 (FABP-4), osteocalcin, aggrecan, SOX2 and oligodendrocyte-4 (Olig-4) markers. The cells were strongly positive for the MSC markers CD29, CD44, CD73 and CD105; these cells also expressed the ESC markers CD9, SSEA-1 and SSEA-4, E-cadherin, PODXL, SOX2, NANOG and OCT3/4. Additionally, the MSCs expressed the adipogenic FABP-4, osteogenic osteocalcin, chondrogenic aggrecan and neural Olig-4 and SOX2 markers after differentiation. Therefore, HUCB is a rich source for MSCs with embryonic characteristics.